Analisis Framing Berita Kasus Diskriminasi Perempuan pada Media Online Suara.Com dan Detik.Com - Neng Tika Harnia; Hendra Setiawan (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2021)
This study aims to determine a media in framing the news. This aspect is seen based on each news content of a media when choosing the title, background information and news source for each news quote. The focus of research is on reporting cases of women's discrimination onmedia onlineSura.com and Detik.com. This study used a descriptive qualitative method. The results of this study indicate that themedia onlineSuara.com seems excessive in choosing diction in each news title regarding cases of women's discrimination. Meanwhile, themedia onlineDetik.com chose news titles that were simple and focused on the content of the news. The conclusion in this study is that each media has a different characteristic and ideology in framing the news.